2012
DOI: 10.1108/17570971211281657
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to treatment: reasons for non‐attendance in women's secure settings

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…These outcomes are broadly comparable with those in other published studies (McMurran and Theodosi, ; Sheldon et al, ; Long et al, ). As refusals out‐numbered dropouts, it appears that optimising the initial assessment is a vital clinical task (Quinsey et al, ; Long et al, ). Our results provided some support for the predictive validity of the internal factors of the MORM, as discussed in the succeeding sections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These outcomes are broadly comparable with those in other published studies (McMurran and Theodosi, ; Sheldon et al, ; Long et al, ). As refusals out‐numbered dropouts, it appears that optimising the initial assessment is a vital clinical task (Quinsey et al, ; Long et al, ). Our results provided some support for the predictive validity of the internal factors of the MORM, as discussed in the succeeding sections.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of patients in a high security psychiatric hospital, Sheldon et al () also found evidence that reasons for treatment non‐completion were consistent with the MORM, specifically, emotional arousal/dysregulation, therapy‐incongruent goal motivation and negative attitudes towards self‐efficacy, treatment and staff. Long et al () assessed treatment engagement among female patients in secure hospitals and also found that cognitive, affective and volitional characteristics were associated with non‐engagement, but behavioural and identity reasons were less so.…”
Section: Introductionmentioning
confidence: 99%
“…A broad definition of noncompletion/engagement was included to ensure all factors influencing treatment engagement were identified. While nonengagement has been commonly attributed to an individual’s lack of motivation or resistance, it has been argued that other reasons, including problems with the treatment environment or legitimate and rational concerns regarding treatment, have often been ignored (Long et al, 2012). Therefore, by using a broad definition of noncompletion/engagement, the current review aimed to address this critique and increase awareness that for some individual’s reasons for and against engaging in treatment, even for just one session, may be attributed to organisational factors as well as client factors.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, among the external factors identified in this review, exclusion from treatment was noted in several studies as the reason for noncompletion of treatment (Long et al, 2012;Polaschek, 2010;Sheldon et al, 2010;Strauss & Falkin, 2000). While this is clearly an external reason, the reasons why participants engaged in particular behaviours that led to expulsion were not explored and likely reflect internal factors.…”
Section: Implications For Future Researchmentioning
confidence: 98%
See 1 more Smart Citation